Spa-therapy can improve quality of life in chronic musculoskeletal disorder subjects: a narrative review - Maccarone, M.C.; Magro, G.; Solimene, U.; Masiero, S. (Bulletin of Restorative Medicine, 2020)
Chronic Musculoskeletal Disorders (MSDs) are age-related conditions, linked to functional impairment and decreased quality of life (QoL). As a result of the increased life expectancy in Europe, great attention has been focused on investigating the impact of these diseases on QoL. Thermal environment is a suitable place for providing interventions (mud therapy, bath, exercise, etc.) for chronic MSD patients. Our narrative review aims to assess if Spa therapy may improve QoL in patients with chronic MSDs. We searched randomized clinical trials and clinical trials screening PubMed and Google Scholar databases from 2016 up to March 2020. We included 14 trials testing Spa therapy interventions concerning osteoarthritis, rheumatoid arthritis, chronic shoulder pain and fibromyalgia. In conclusion, even though limitations must be considered, evidence shows that Spa therapy, especially in combination with rehabilitation approach, can significantly improve QoL of patients with chronic MSDs.